Implementation of Problem-Based Learning Models to Critical Thinking Ability of Primary School Students in Citizen Education Learning - Nurfaizah, Izah; Yuliyanto, Aan; Nurjanah, Nunung; Fitriyah, Rizky; Wiratno (International Conference on Elementary Education, 2024)
In teaching and learning activities, educators are still not optimal in applying problem-based methods. Critical thinking is needed to find a way out of these problems regarding students' responses to teachers. Critical thinking is analyzing problems in an idea to find solutions. Five indicators of critical thinking namely: analyzing problems, being able to ask and answer questions, solving problems, making conclusions, and evaluating or assessing observation results. This literature review discusses the impact of implementing a problem-based learning model on elementary school students' critical thinking skills in learning citizenship education. This problem-based learning model is proven to be able to improve student's critical thinking skills, be able to present problem orientation for students so they can understand learning objectives and solve problems, organize students in group discussions, guide group investigations so they can look for problems that are presented, develop and present work results so that Students can prepare reports on discussion results, analyze and evaluate the problem-solving process so that teachers and students can evaluate the problem-solving process in learning. Critical thinking is seen as essential and developed in schools so that students are accustomed to dealing with various problems around them.